Human resource management in hospitality cases - Szende, Peter; Bagnera, Suzanne Markham; Cole, Danielle Clark (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Human Resource Management in Hospitality Cases adopts a practical case-based approach to develop critical thinking and problem-solving skills in future hospitality managers. Using tried-and-tested real-life scenarios, this book thoroughly prepares hospitality students for a career in the field. Chapters are comprised of 75 short vignettes, split into 9 sections that reflect and cover the primary challenges facing hospitality managers on a daily basis including; leadership credibility, building and managing employee performance, managing a diverse workforce, dealing with problem behaviours and many others, all contextualised within the hospitality industry. With a main 'think point' and series of questions for each case, the book is a highly insightful and engaging read. Suggested answers and solutions to the questions can be found within the extensive online resources that complement the book. Each section is also contextualised and theorised with an additional reading section, organised by key concept. This book will be essential for all students of hospitality and an invaluable resource for current practitioners in the field as well"--
OCLC-licensed vendor bibliographic record.
Keywords: Hospitality industry -- Management -- Case studies; Critical thinking -- Case studies; Personnel management -- Case studies; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism